2019
DOI: 10.1038/s41598-019-43130-9
|View full text |Cite
|
Sign up to set email alerts
|

3D analysis of the whole subcutaneous adipose tissue reveals a complex spatial network of interconnected lobules with heterogeneous browning ability

Abstract: Adipose tissue, as the main energy storage organ and through its endocrine activity, is interconnected with all physiological functions. It plays a fundamental role in energy homeostasis and in the development of metabolic disorders. Up to now, this tissue has been analysed as a pool of different cell types with very little attention paid to the organization and putative partitioning of cells. Considering the absence of a complete picture of the intimate architecture of this large soft tissue, we developed a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
4
18
0
Order By: Relevance
“…Hence, functional clustering reveals the existence of an unexpected organization scale inside large clusters. Consistent with our previous reports [47] [48], this finding clearly emphasizes the heterogeneity of adipose tissue and its multiscale organization particularly for the oxidative metabolism point of view that strongly depends on vasculature and perfusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hence, functional clustering reveals the existence of an unexpected organization scale inside large clusters. Consistent with our previous reports [47] [48], this finding clearly emphasizes the heterogeneity of adipose tissue and its multiscale organization particularly for the oxidative metabolism point of view that strongly depends on vasculature and perfusion.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, various structural graph properties (such as centrality and authority) were strongly correlated with local anatomic features (vascular density, vessel connections) as well as functional features (total blood perfusion and exchange flux perfusion time). The primacy of these vascular-based network parameters near the lymph node region is highly associated with the high browninggene expression found in [48], thus corroborating the well-described relationships between vascularization and the browning process. Hence, we found a vascular-based body of evidence for the existence of a central, well-perfused, strongly-connected and, highly-coupled region of adipose tissue as opposed to the more unstructured, poorly-connected, peripheral organization.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…These immune clusters provided the first evidence of a direct role of fat immune cells in anti-infectious responses, and also highlight the "regionalization" of AT. In fact, AT is a vascularized tissue that is organized into several lobular unit (Tang et al, 2008;Walker et al, 2008;Chi et al, 2018;Dichamp et al, 2019). These partitioned areas exhibit specific metabolic (and probably immune) activities.…”
Section: Specific Features Of Adipose Tissue the Anatomic And Functiomentioning
confidence: 99%
“…while others have shown that browning commonly occurs around LNs (61). Furthermore, all lymph nodes in the body are surrounded by adipose tissue, which is activated during an immune response (62).…”
Section: Discussionmentioning
confidence: 99%